Minorías étnicas en el servicio exterior ecuatoriano: un análisis crítico del proceso de incorporación de Terceros Secretarios 2012-2015 - Pava Bonilla, Edgar Lenin (2016)
This research analyzes the link between international relations and discrimination based on ethnicity and gender for it is used in the case of inclusion of ethnic minorities with gender equity occurred in the ecuadorian diplomacy. The research makes a tour through the constructivist theory, the dynamics of power and racism, feminism and multiculturalism. These and other theories are linked to political, social and legal changes experienced in recent years in Latin America. An analysis of the construction of the institutional identity of the Ministry of Foreign Affairs and Human Mobility of Ecuador is done from the voices and perceptions of its officials, the press and people who were part of this unprecedented process for Ecuador's diplomacy and posed commissioning practice of constitutional principles of multiculturalism and multi-nationality in the international context.